Analysis of Waste Management Programs to Increase Environmental Awareness of the Youth Generation - Kania Saraswati Harisoesyanti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This article will discuss the role of youth in community development programs. The waste management programs were conducted in two districts in West Java, Indonesia, namely CK and PMin Depok. Youth and stakeholders serve as informants in this study, which employs a qualitative research method. The process of implementing and evaluating these waste management initiatives begins with engagement. Several factors influenced young people's involvement in this community development program, including the youngsters themselves and their environment. In each of these programs, growing awareness of the necessity of waste management underpinned youth involvement and could not be isolated from youth personal issues, as well as contact between youth and adults in the community, which had a significant impact on the program. How kids engage with environmental concerns is contingent on their response to problems, challenges, and opportunities, none of which occurred suddenly, but rather constantly.